Z tradycją w przyszłość. Pedagogika społeczna wobec przemian cywilizacyjno-kulturowych. Czterdziestolecie Katedry Pedagogiki Społecznej Uniwersytetu Śląskiego w Katowicach - Jarosz, Ewa; Syrek, Ewa (Chowanna, 2019)
The article presents the development, directions and areas of scientific research conducted by scholars at the Department of Social Pedagogy at the University of Silesia in Katowice from the beginning of the Department’s existence (1980/1981) until 2018. The conducted analyses emphasize first of all the expansion of research areas and the successive formation of the so-called “school” of social pedagogy characteristic of our academic centre. The areas of interest of the Department’s research staff correspond to the cognitive and research needs resulting from the current socio-cultural transformations that are significant for the course of socialization and upbringing processes. The results of scientific research have been reflected, among others, in scientific publications (monographs and articles), and the titles of the most important ones are given in the article.